Pelatihan Dasar Kaligrafi Dalam Memperkenalkan Teknik Tulis Al-Qur’an pada Murid MTs Darussalam Ibrahimy Desa Sumberkokap Kecamatan Taman Krocok Kabupaten Bondowoso - Rifqatul Husna; Fairuz Vera; Ach. Zayyadi; Ghurratul Muhajjalin (LPPM STIE Ganesha, 2025)
The basics of calligraphy writing in the form of hijaiyah letter writing techniques are training that needs to be held in schools, especially in schools that focus on Islamic religious education, because they are the basis of the techniques for writing the Koran. This service is training in basic techniques for writing the Koran at MTs Darussalam Ibrahimy, Sumberkokap Village, District. Krocok Park, Kab. Bondowoso, East Java. MTs Darussalam Ibrahimy is a first-level secondary education institution that has a strong focus on Islamic religious education. The problem faced in this school is the lack of guidance in learning hijaiyah letter writing techniques, as well as the students' low interest in this writing technique, because they think that writing Arabic, the language of the Koran, does not have certain techniques so they are careless in writing. Hijaiyah letters. This form of service is carried out through intensive training and coaching for basic calligraphy practices to introduce hijaiyah letter writing techniques correctly. The proposed solution includes an introduction to basic calligraphy techniques in the form of procedures for writing hijaiyah letters starting from the letter alif to the letter ya'. The implementation of this service begins with the observation method by gathering information about Al-Qur'an writing activities at MTs Darussalam Ibrahimy and to achieve the achievement targets set during the service, it continues with preparation and coordination, education and finally evaluation. The result obtained from this service is an increase in students' ability to write hijaiyah letters according to the rules of writing the Koran, although it is still far from the expected target. Their views on Arabic writing are starting to change, they no longer think that Arabic writing does not have certain techniques so they are careless in writing hijaiyah letters.